The Transformation of Mexican Agriculture : International Structure and the Politics of Rural Change. - Sanderson, S. (Princeton legacy library., 2014)
In spite of the most thorough agrarian reform in nonsocialist Latin America, Mexico cannot feed its population. Steven Sanderson attributes the problems of Mexican agriculture to an internationalization of the food system promoted by the Mexican state, the trade system, and agribusiness. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these importan.